REORIENTASI KURIKULUM PAI DI MADRASAH: STUDI ANALISIS LANDASAN PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Muhammad Arbain; Badrut Tamam (Reflektika, 2017)
Islamic religious education curriculum must have a strong foundation in its development process. The foundation plays important role to maintain the curriculum. Therefore, the curriculum developers need to establish a firm foundation in curriculum development used in madrasahs. This paper employs descriptive-analysis method in finding the foundations of the curriculum. Result shows that there are seven basic foundations in developing the curriculum, theological foundation (religion), philosophical foundation, ideological foundation, psychological foundation, sociological foundation, science and technology foundation and organizational foundation. With those foundations, madrasahs now have the firm base to foundation in determining the direction for their institutions and remain upright from the onslaught of globalization. The foundations will at least make madrasahs future-oriented in the development of Islamic civilization both nationally and internationally.